CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM FUND DISTRIBUTION MODEL IN COMMUNITY ECONOMIC EMPOWERMENT EFFORTS - Mabruroh (IZZI: Jurnal Ekonomi Islam, 2026)
Corporate Social Responsibility (CSR) is a company's commitment to supporting sustainable economic development by considering the balance between economic, social, and environmental aspects. This study aims to describe the model of CSR program fund distribution in efforts to empower the community economically at Yasmin Hospital in Banyuwangi, East Java. The focus of the study includes: (1) the model of CSR fund distribution for community economic empowerment, (2) the model of community economic empowerment related to CSR fund distribution, and (3) the positive implications of both models. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis included data reduction, data presentation, and conclusion drawing with data validity through triangulation. The results of the study show that the CSR fund distribution model of Yasmin Hospital is able to improve the welfare and economic independence of the community and contribute to environmental preservation, although it still needs improvement to be more effective and efficient in terms of time, cost, and energy.